Pengaruh Kecepatan Dan Waktu Pengadukan Lambat Terhadap Penyisihan Fosfat Dan TSS Limbah Cair Laundry Menggunakan Biokoagulan Tepung Biji Asam Jawa - Ribka Hutapea; Syarfi Daud; Edward Hs (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Tamarind seeds are biocoagulants which contain active substances and are polyelectrolytes. This study aims to determine the slow stirring speed and stirring time in the removal of phosphate and TSS parameters in laundry wastewater and to compare the analysis results with the PERMENLH / 5/2014 quality standard. The removal was carried out by coagulation flocculation and sedimentation using tamarind seed flour by varying the slow stirring speed of 40 rpm, 45 rpm, 50 rpm and slow stirring time of 20 minutes, 25 minutes, 30 minutes and fast stirring 120 rpm for 3 minutes, with a biocoagulant dose 3.5 gr/l. The results showed that the optimum stirring speed was 45 rpm with a stirring time of 25 minutes with the removal efficiency of 60.59% and 78.50% TSS, respectively. The analysis results for phosphate and TSS still do not meet the quality standards for laundry wastewater. Keywords: Laundry Liquid Waste, Stirring Speed, Stirring Time, Coagulation-Flocculation, Tamarind Seed Flour